Penyelesaian Masalah Limit Fungsi dengan Menggunakan Software MATLAB (Matrix Laboratory) - Mikolis Etimanta Ginting; Eka Sri Hartini Hasibuan; Danu Rama Dani; Nia Devi Friskauly; Witri Wardani Hulu (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2024)
The solutions of limit problems is one of fundamental concepts in real analysis, applicable in various fields of mathematics and other sciences. However, determining limit can sometimes present challenges, particularly when the fuction in question is complex and difficult to solve manually. This study demostrates the use of MATLAB as a tool to assist in solving such problems numerically. The findings show that MATLAB is realible in calculating the limits of specific fuctions, offering accurate solutions more efficiently and quickly compared to manual methods.